Strategi Guru dalam Mengembangkan Pembelajaran Mendalam (Deep Learning) pada Pendidikan Anak Usia Dini - Annafi Nurul Ilmi Azizah; Rahma Widia Wati; Vitaria Aqatha; Dewi Andini Nurhayati; Anisatur Rofiah; Meyda Setyana Hutami (E-JURNAL AKSIOMA AL-ASAS, 2026)
This study aims to describe teachers’ strategies in developing deep learning in early childhood education. The research employed a descriptive qualitative approach involving teachers at TK Insan Kamil Sukoharjo as research subjects. Data were collected through in-depth interviews and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings revealed that teachers implemented the principles of mindful, meaningful, and joyful learning through triggering questions, simple experiments, flexible thematic learning, and the use of concrete media and the surrounding environment. These strategies increased children’s active participation, creativity, critical thinking skills, and self-confidence. In addition, differentiated learning strategies helped accommodate children’s diverse learning needs and characteristics. Deep learning was considered effective when supported by teacher competence, flexible planning, and a conducive learning environment.